2005
DOI: 10.1302/0301-620x.87b1.15096
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentous repair and reconstruction for posterolateral rotatory instability of the elbow

Abstract: We describe the intermediate results of lateral ligamentous repair or reconstruction for posterolateral rotatory instability of the elbow. Between 1986 and 1999, we performed 12 direct repairs and 33 ligament reconstructions with a tendon autograft. One patient was lost to follow-up and 44 were retrospectively studied at a mean of six years (2 to 15).Surgery restored stability in all except five patients. In two the elbow became stable after a second procedure. The mean post-operative Mayo elbow performance sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
109
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(118 citation statements)
references
References 17 publications
2
109
0
7
Order By: Relevance
“…If they are torn and can not be re-paired, reconstruction of the ligament using palmaris longus tendon is recommended. 13 In our experience, primary stabilization is preferred than late reconstruction procedure, because primary repair immediate after injury can avoid complicated reconstruction procedure with early return to previous work activities.…”
Section: Discussionmentioning
confidence: 92%
“…If they are torn and can not be re-paired, reconstruction of the ligament using palmaris longus tendon is recommended. 13 In our experience, primary stabilization is preferred than late reconstruction procedure, because primary repair immediate after injury can avoid complicated reconstruction procedure with early return to previous work activities.…”
Section: Discussionmentioning
confidence: 92%
“…However, thanks to scientific advances options for surgical reconstruction of the soft tissues of the elbow have multiplied in recent years (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), so discussion of standard treatment for simple elbow dislocation has been rekindled.…”
mentioning
confidence: 99%
“…Sanchez-Sotelo et al 17 in 2005 reported that reconstruction using a tendon graft seems to provide better results than ligament repair and the results do not seem to deteriorate with time. Jones et al 18 reported good results using a docking technique for reconstruction of the LUCL in patients with PLRI, with a low complication rate.…”
Section: Discussionmentioning
confidence: 99%